Functioning Anarchy: India’s National Telecommunications Policy and the Development of Basic Telephone Services - Swaminathan, Rajesh (Columbia Journal of Asian Law, 1997)
The Government of India’s (GOI) efforts to implement its 1994 National Telecommunication Policy are perhaps most appropriately summed up by paraphrasing John Kenneth Galbraith’s memorable assessment of India: as he said of the country, one may say of the Policy that it is “functioning anarchy.” Since its articulation by the Congress (I) government of Prime Minister P. V. Narasimha Rao, it has been shown to be haphazardly conceived, modified on an ad hoc basis, badly implemented and abused for private gain. Nevertheless, in its own perveise way, it has made possible the incremental and still incomplete, but probably irreversible, liberalization of the telecommunications sector. Nowhere is this paradox more evident than in the government’s efforts to promote the development of “basic” telecommunication services, as envisioned in the Policy. From the outset, this endeavor has been crippled by enduring conflicts of interest, a sometimes stunning incomprehension about the technical aspects of the telecommunications industry, an intermittent disregard for economic analysis and a vestigial loyalty to the Fabian socialism of the Nehruvian state. In this paper, I attempt to survey this process of reform, and to offer some tentative assessments of its irregular progress.